Homocystinemia Leading to Bright Facial Colliculus - A Rare Entity in Young Adults (Global Journal of Medical Research, 2014)
he facial colliculus is an elevated area located on the dorsal pons in the floor of the 4th ventricle. It is produced by the nucleus of the abducens nerve and the flexure of the facial nerve around it. Any lesion involving the abducens nucleus cause the disorder of internuclear ophthalmoplegia (INO) which is characterized by ipsilateral adduction deficit and the preservation of abduction of the contralateral eye when the patient tries to look in the contralateral direction. Isolated infarction of facial colliculus effecting abducens nucleus is very rare [1].